Система захисту від обриву проводу та пошук місця пошкодження в розподільних мережах напругою 6–35 кВ - Кутіна, М.В. (Технічна електродинаміка, 2012)
A protection system based on measurement of current reverse sequence to the fall-to-ground, measured zero sequence voltage after falling to the ground wire locating and applying the method to determine the site of injury. In theory, setting reasonable wear protection and method of processing information in locating method. Shown the effectiveness of the proposed system of protection against breakage of the wire that is to reduce the time searching site of injury, increasing reliability and safety.